Indonesian Learner’s Perception of Using Fondi Application in Fostering Their English-Speaking Skill - Musyafa Syamil Arroyan; Wijayanti Ma'rufah, Desi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
English has become an important language to master in the era of globalization. Among the challenging skills in learning English, speaking is one of the most difficult skills to master. In today's era, the development of speaking skills is facilitated by technological advances. Despite this, students still face challenges in choosing the right technology to achieve their desired language proficiency. This research aims to explore user perceptions of the Fondi application as a platform for learning speaking skills. Participants in this research consisted of 34 Fondi application users. This research uses the Concurrent Embedded Strategy mix method methodology. In obtaining data, there were 2 techniques used in this research, namely through questionnaires and interviews. The questionnaire uses closed questions which function to ask the main/core questions. After that, interviews were conducted to confirm answers and obtain more detailed information. Next, the data is analyzed and processed using predetermined formula. Research findings show that users have a positive perception of the Fondi application, as many as 15 people (44.12%) fall into the 'very high' range and 19 people (around 55.88%) fall into the 'high' range. These results result in the conclusion that users generally have a good perception of the Fondi application. In addition to investigating user perceptions, this study contributes to the literature on the Fondi application, addressing an important gap in current research. For future research, this study suggests that next research should be followed up with effectiveness testing using an experimental model to measure how effective this application in improving learner’s English ability accurately. Such testing would strengthen the findings presented in this article. Lastly, each variable asked can be discussed in more detail in further research. Future studies can use samples from a larger population so that they can be more representative.